Towards an integrated process for digital transformation: 5G and beyond based smart transportation systems in cities and regions - Risto Jurva; Tarja Outila; Marja Matinmikko-Blue; Virve Merisalo; Johannes Jutila (International Telecommunications Society (ITS), 2022)
Digitalization is transforming businesses and daily lives at an increasing rate. Cities and regions are going through a digital transformation process to develop and deploy a range of digital services covering most city functions and operations. The different operations are inter-dependent and are all constrained by new sustainability requirements. This paper investigates digital transformation in the context of future smart transportation systems in cities and regions and focuses on the situation in Finland. The paper analyses the current processes of urban design and planning, transportation planning, and digital infrastructure planning and brings them together towards a future process for smart transport system planning. The paper provides guidelines for the development of this interlinked future process for digital transformation and discusses related challenges. The integrated process highlights the importance of bringing together the traditionally separately considered urban design and planning, transport system planning and digital infrastructure planning processes by starting from shared values, goals and strategies that are built on sustainability principles. This requires the identification of a system owner, which has the overall responsibility of system development and operation.
Keywords: 330